The relativity of the abstract feature of negotiable instruments with an emphasis on judicial procedure - Reza Mirtaheri; Hossein Taherkhani; Davood Andarz (مطالعات فقه و حقوق اسلامی)
The separation of negotiable instruments from the civil obligation is the separation between two legal relationships, which is called abstract presumption. The most important aspects of this presumption: indebtedness and lack of attention to flaws in the private relations of the parties, which is called relative presumption. Although the commercial law of Iran has not explicitly accepted the fact that negotiable instruments are abstract, it can be inferred from the spirit of some laws, but some side examples cannot be considered absolute in the absence of the ability to invoke flaws against a third party, because exceptionally, it is assumed by the legislator to protect the third party. In order to achieve a logical attitude, the relativity of the abstract presumption should be examined according to the concept of the presumption and the principle of uncertainty of the presumptions and their opposability from the perspective of jurists, law, and judicial procedure. The judicial procedure has accepted this relativity, unlike some harsh attitudes in the field of turning civil obligation into commercial obligation.